Les paysages de champs surélevés de Guyane française : un patrimoine bioculturel menacé - Stéphen Rostain; Doyle McKey (Revue d'ethnoécologie)
The coastal savannas of the Guianas harbor extensive areas covered with vestiges of pre-Columbian raised-field agriculture. Recent studies have shown their value in documenting the history of human occupation and environments in the region. In the case of French Guiana, few of the present-day inhabitants are aware of the existence of these vestiges, and those who are have little appreciation of their significance. Thus the manifold dangers this biocultural heritage faces have largely gone unnoticed and unchallenged, and few raised-field vestiges are included in protected areas. The objective of this paper is to document the richness of these landscapes, illustrate their value, and draw attention to the threats facing them. We argue that they merit greater protection.